The Effect of Service Quality on Patient Loyalty Through Patient Satisfaction at the Dental and Oral Clinic of Mitra Kasih Hospital Cimahi - Nuryanti, Nuryanti; Paramarta, Vip; Rahmiyati, Ayu Laili (Poltekkes Kemenkes Riau, 2025)
These findings suggest that improving service quality, both in terms of facilities and interactions between medical staff and patients, plays a crucial role in enhancing patient satisfaction and loyalty. This study offers practical contributions to hospital management, developing strategies to enhance service quality and maintain and improve patient satisfaction and loyalty. This study aims to analyze the effect of service quality on patient loyalty, as measured by patient satisfaction at the Dental and Oral Clinic of Mitra Kasih Hospital Cimahi. This study aims to analyze the effect of service quality on patient loyalty through patient satisfaction at the Dental and Oral Clinic of Mitra Kasih Hospital Cimahi. The research is based on a significant decline in the number of patients in recent years, especially during the COVID-19 pandemic, as well as complaints about the quality of hospital services. A quantitative approach with descriptive and verificative design was applied, involving service quality (X), patient satisfaction (Y), and patient loyalty (Z) variables. Data were collected through structured questionnaires distributed to a sample of patients and analyzed using path analysis. The results indicate that service quality has a positive and significant effect on patient satisfaction (0,875), which in turn influences patient loyalty (0,595). Patient satisfaction also influences on patient loyalty (0.733). Moreover, there is a significant indirect effect of service quality on patient loyalty through patient satisfaction as an intervening variable (1,9876). The key factors contributing to patient satisfaction include reliability, responsiveness, assurance, empathy, and tangible aspects of the service.